DESAIN TATA DISPLAY PASAR BUAH SEBAGAI DAYA TARIK WISATA BELANJA DI PASAR GEDHE HARDJONAGORO - Ahmad Fajar Ariyanto; Alexander Nawangseto Mahendrapati (PROSIDING: SENI, TEKNOLOGI, DAN MASYARAKAT, 2019)
Traditional market in Surakarta is still preserved and being part of economic activity of the society, despite the increasing number of supermarkets. The revitalization of these markets is one of the medium-term development plans of Surakarta because compared to the other sources, traditional markets make the biggest contribution to the local government revenue. One of these markets is the western part of Pasar Gedhe Hardjonagoro whose commodities are fresh fruits. Unfortunately, the rehabilitation and renovation program are only focused on the main building. The inside area where the trade activities between sellers and buyers happen is excluded from the rehabilitation program. Considering Pasar Gedhe as a tourist destination, the needs of market management especially for displaying the product is essential to attract the consumers and tourists. This article is the result of an applied research in interior design about the design of display system of fruit sellers in the western part of Pasar Gedhe Hardjonagoro in Surakarta. This applied research is a qualitative descriptive analysis with case study approach. The work employs functional, ergonomic, thematic, and stylish approaches for the design solution. The result acquired from the interior design research is a zoning which is divided into selling, circulation and service, outdoor zone, and managing the circulation and two-side services, and creating the interior theme. While the result on the display design is the design needs to be able to functionally support the trade activities, easy to maintenance, solid, longlasting, safe, the display system represents the locality, and how the commodities can be an interesting visual attraction. The display system is designed to be an open layout system so that it creates a socio-cultural interaction for the people within the market.